Reason, Justice and Dignity : a Journey to Some Unexplored Sources of Human Rights. - Leuprecht, Peter (BRILL, 2011)
The book takes the reader on a journey to unexplored sources of human rights: ancient China, the golden age of Islam and 16th century Spain. All three share a strong belief in reason, justice and human dignity.